A retrospective analysis of the effect of intraoperative opioid dose on cancer recurrence after non‐small cell lung cancer resection. (2nd April 2014) - Cata, Juan P.; Keerty, Visesh; Keerty, Dinesh; Feng, Lei; Norman, Peter H.; Gottumukkala, Vijaya; Mehran, John R.; Engle, Mitchel
Abstract Preclinical studies have demonstrated that opioid receptor agonists increase the rate of non‐small cell lung cancer (NSCLC) growth and metastasis. Following institutional review board approval, we retrieved data on 901 patients who underwent surgery for NSCLC at MD Anderson Cancer Center. Comprehensive demographics, intraoperative data, and recurrence‐free survival (RFS) and overall survival (OS) at 3 and 5 years were obtained. Cox proportional analyses were conducted to assess the association between intraoperative opioid exposure and RFS and OS. The median intraoperative fentanyl equivalents dosage was 10.15 μg/kg. The multivariate analysis by stage indicated that a trend toward significance for opioid consumption as a risk factor in stage I patients (P = 0.053). No effect was found on RFS for stage II or III patients. Alternatively, opioid consumption was a risk factor for OS for stage I patients (P = 0.036), whereas no effect was noted for stage II or III patients. Intraoperative opioid use is associated with decreased OS in stage I but not stage II–III NSCLC patients. Until randomized controlled studies explore this association further, opioids should continue to be a key component of balanced anesthesia.